New housing registrations as a leading indicator of the BC economy - Calista Cheung; Dmitry Granovsky (Bank of Canada, 2016)
Housing starts and building permits data are commonly used as leading indicators of economic activity. In British Columbia, all new homes must be registered with the Homeowner Protection Office, a branch of BC Housing, before the issuance of building permits and the start of construction. Data on new housing registrations (NHR) could thus potentially be used as an even earlier leading indicator of economic activity. This study assesses whether NHR data have significant predictive power for economic activity in British Columbia. The authors find that quarterly increases in new registrations for single detached homes have statistically significant predictive content for growth in real GDP over the next one to three quarters, and provide stronger signals compared to housing starts and building permits over this forecast horizon. These signals remain significant for growth in real GDP over the next two quarters even in the presence of other leading indicators in the equations. However, forecasts using quarterly NHR data with other leading indicators are not able to outperform simple benchmark forecasts in an out-of-sample forecasting exercise. Nonetheless, adding the NHR variable to an AR(1) equation does produce forecasts that are superior to a simple AR(1) and that at one quarter ahead also outperform an AR(1) augmented with building permits.
Keywords: C13; C53; E32; E37; 330; Business fluctuations and cycles; Housing; Regional economic developments